Draft Annual Plan 2008-2009 Maharashtra State Part II - Planning Commission (Planning Commission, 2008)
A-Economic Services Rural Development Irrigation and flood control Energy Industry and minerals Transport Science and technology and environment General Economic services B-Social services -General services.
Government of Maharashtra Planning Department